1998
DOI: 10.1203/00006450-199810000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Environmental Exposure to Polychlorinated Biphenyls and Dioxins on Birth Size and Growth in Dutch Children

Abstract: Lower birth weight and growth retardation has been found in studies with laboratory animals, in children born of mothers exposed to accidental high levels of polychlorinated biphenyls (PCBs) and related compounds, and in children born of mothers who consumed PCB-contaminated fish. The effect of background exposure to PCBs and dioxins on birth size and growth in human newborns, however, is still unknown. This study examined birth size and postnatal growth of term newborns in relation to their background PCB and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
163
8
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 243 publications
(184 citation statements)
references
References 31 publications
9
163
8
2
Order By: Relevance
“…In human studies, maternal contamination with PCBs has been reported to be associated with low birth weight (Fein et al, 1984;Patandin et al, 1998;Rylander et al, 1998), smaller head circumference (Fein et al, 1984), shorter height in males (Dewailly et al, 1993) and shorter gestational length (Fein et al, 1984;Taylor et al, 1989), although results have not been consistent. Our aim was to investigate a range of adverse reproductive outcomes in women, using breast milk PCB concentration as a measure of body burden.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations
“…In human studies, maternal contamination with PCBs has been reported to be associated with low birth weight (Fein et al, 1984;Patandin et al, 1998;Rylander et al, 1998), smaller head circumference (Fein et al, 1984), shorter height in males (Dewailly et al, 1993) and shorter gestational length (Fein et al, 1984;Taylor et al, 1989), although results have not been consistent. Our aim was to investigate a range of adverse reproductive outcomes in women, using breast milk PCB concentration as a measure of body burden.…”
Section: Introductionmentioning
confidence: 98%
“…Polychlorinated Biphenyls (PCBs) a group of polycyclic chlorinated hydrocarbons, are widespread environmental contaminants (Fein et al, 1984;Patandin et al, 1998), likely to possess oncogenic and teratogenic properties (Lackmann et al, 1996). PCBs consist of mixtures of 210 different isomers with various degrees of chlorination.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the relationships between individual biological measurements of exposure and birth weight were not clarified, and head circumference was not used as an index of fetal growth in these surveys. In a Dutch population-based study with the background level of exposure, Patandin et al (1998) showed inverse association of cord/maternal plasma PCBs with birth weight and growth rate, including head circumference, from 0 to 3 months of age, but they did not investigate the relationship between maternal TCDDs/TCDFs levels and newborn size. At that time, dioxins in breast milk were quantified as the dioxin toxic equivalent (TEQ), which was then multiplied by the duration, in weeks, of breast feeding to obtain an index of postnatal exposure.…”
Section: Introductionmentioning
confidence: 98%